A study of the developer's liability on abandoned projects in Malaysia / Ros Adleen Othman, Wan Rosalili Wan Rosli - Othman, Ros Adleen; Wan Rosli, Wan Rosalili (2007)
Housing development can be regarded as the main industry in Malaysia since it gives a big impact to our society especially in the economic, social and politics aspect. Our government has focused on various housing projects in both urban and rural areas in providing affordable housing to the public. Beside that, the government also relies on the private sector to achieve their vision to provide the sufficient accommodations in terms of housing to the public especially house buyers. Therefore, the private sector has contributed efforts to help in producing sufficient housing to the house buyers but due to certain circumstances, problems still occurs when the private developers itself has commit various offences in this industry. According to our research, there are various reasons of the abandonment of housing projects by the private developers for example the failure to complete the housing projects within the stipulated time agreed in the agreement. This study also reviews the statistics on abandonment of housing projects by private developers in Malaysia. Interviews have been carried out and data have been collected from the Ministry of Local Government and Housing (MHLG) and the Real Estate and Housing Development Association (REHDA). The data includes the categories of abandoned projects and factors that lead to the abandonment of those projects. This study also will provide recommendations in order to control and reduce the statistics of abandoned housing projects by the private developers.